Effects of dietary Vitamin E level and source on sow, milk, and piglet concentrations of α-tocopherol - N W Shelton; H Yang; D C Mahan; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
A total of 126 gilts and sows (PIC 1050) and their litters were used to determine the effect of dietary vitamin E level and source on sow plasma, milk, and piglet tissue concentrations of Î±-tocopherol. The 6 dietary treatments included 2 levels of dl-Î±- tocopherol acetate (Syn E) at 44 and 66 mg/kg (40,000 and 60,000 mg/ton) and 4 levels of d-Î±-tocopherol acetate (Nat E) at 11, 22, 33, and 44 mg/kg (10,000, 20,000, 30,000 and 40,000 mg/ton). From breeding through d 69 of gestation, sows were fed 4.5 lb/d of a diet containing 40% dried distillers grains with solubles (DDGS), 0.30 ppm added Se, and no added vitamin E. Vitamin E treatments were fed from d 70 of gestation through weaning (d 21). Plasma was collected from sows on d 69 and 100 of gestation, at farrowing, and at weaning. Colostrum (d 1) and milk samples (weaning) were also collected. Plasma from 3 pigs per litter and heart and liver samples from 1 pig per litter were collected at weaning. All plasma, milk, and tissue samples from 6 sows and litters per treatment were analyzed for Î±-tocopherol.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; Î±-tocopherol; Bioavailability; Natural vitamin E; Sow